2014
DOI: 10.1021/je401008s
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Coefficients of CO2 and N2 in Water at Temperatures between 298.15 K and 423.15 K at Pressures up to 45 MPa

Abstract: We report measurements of the diffusion coefficients of CO2 and N2 in pure water at temperatures between (298.15 and 423.15) K and pressures between (15 and 45) MPa. The measurements were made by the Taylor dispersion method and have a standard relative uncertainty of 2.3 %. The results were found to be essentially independent of pressure over the range investigated and a simple relation, based on the Stokes–Einstein equation, is proposed to correlate the experimental data. Some experimental difficulties arisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
154
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 188 publications
(170 citation statements)
references
References 33 publications
15
154
0
1
Order By: Relevance
“…This behavior is primarily driven by the change in solvent's density, which is marginal at conditions well below the critical point but becomes substantial for high pressures and temperatures. This analysis is in line with the findings of recent experimental [63,64] and computational [57] studies for gases dissolved in H 2 O.…”
Section: Diffusion Coefficients Of Ch 4 and N-c 4 H 10 In H 2 O At Hisupporting
confidence: 91%
“…This behavior is primarily driven by the change in solvent's density, which is marginal at conditions well below the critical point but becomes substantial for high pressures and temperatures. This analysis is in line with the findings of recent experimental [63,64] and computational [57] studies for gases dissolved in H 2 O.…”
Section: Diffusion Coefficients Of Ch 4 and N-c 4 H 10 In H 2 O At Hisupporting
confidence: 91%
“…15 and 423.15) K and at pressures up to 45 MPa. 2 The results were correlated to within ± 4 % with eq 5 by making the hydrodynamic radius a weak linear function of temperature as follows:…”
Section: Discussionmentioning
confidence: 95%
“…2,3 In the absence of salts, a single diffusion coefficient fully describes the mutual diffusion of CO 2 and water in the system. When the CO 2 is dissolved in a brine, there are at least three diffusing components: CO 2 , salt, and H 2 O. Diffusion can be described in the Fickian formalism by means of the following relations where there is no net molar flux with respect to the coordinate system:…”
Section: Introductionmentioning
confidence: 99%
“…[27][28] In a recent study, Cadogan et al 15 reported experimental measurements for infinitely diluted CO2 in various alkanes (n-hexane, n-heptane, n-octane, n-decane, n-dodecane, nhexadecane and squalane) obtained by the Taylor Dispersion method. 61 In the present work, we focus on simulations of the diffusion coefficients of infinitely diluted TraPPE CO2 in most of these alkanes, namely: n-hexane, n-decane, n-hexadecane, cyclohexane and squalane. The intermediate-length linear alkanes are expected to follow similar trends as the systems studied here.…”
Section: Diffusion Coefficient and Viscosity Calculations The Diffusmentioning
confidence: 99%